2016
DOI: 10.7860/jcdr/2016/20798.8498
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Dystrophy of the Duodenum Due to Heterotopic Pancreas – A Case Report and Review of Literature

Abstract: A 47-year-old male with history of alcohol abuse for 8 to 10 years visited the Department of Gastrointestinal Surgery for recurrent attacks of mild acute pancreatitis since 3 years. He also had recurrent epigastric pain, significant weight loss, early satiety and postprandial fullness. Multiple ultrasonography examinations and Computed Tomography (CT) scans of abdomen done in the past suggested chronic pancreatitis for which patient was advised pancreatic enzyme supplementation, alcohol abstinence, analgesics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…These CT signs and a medical history of alcohol abuse are highly suggestive of GP. In a case report (46), the patient, having a 10-year history of alcohol abuse, and history of recurrent acute pancreatitis was examined by CT.…”
Section: Ctmentioning
confidence: 99%
“…These CT signs and a medical history of alcohol abuse are highly suggestive of GP. In a case report (46), the patient, having a 10-year history of alcohol abuse, and history of recurrent acute pancreatitis was examined by CT.…”
Section: Ctmentioning
confidence: 99%
“…In our systematic review of 17 studies (Table 3) with 146 patients of which 143 (98%) underwent PD, complete resolution of symptoms was achieved in more than 80% of patients whilst the remaining 20% achieved some improvement of their preintervention symptoms over a 31 month follow up. 7,9,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] The major morbidity and mortality rates were 5.5% and 2% respectively, with a clinically significant pancreatic fistula rate of 3.5%. This demonstrates that PD can be performed safely, with acceptable outcomes despite a higher technical difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies were included for final review, comprising 146 patients with histopathologically confirmed GP. 7,9,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Mean age was 42.1 years; 79% of patients were male. 9,11,[15][16][17][18][19][20][22][23][24][25][26][27] A smoking history was significant in 71% of patients (95% CI: 46%-88%).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still unclear and contentious whether Groove pancreatitis and cystic duodenal dystrophy are distinct entities or part of the same spectrum. Hence, the term "Paraduodenal Pancreatitis (PDP)" has been proposed to include Groove pancreatitis (solid subtype), cystic dystrophy of the duodenum and paraduodenal cysts (cystic subtype, [15,16]).…”
Section: Gross (Morfological and Imaging) Examination And Classificationmentioning
confidence: 99%